Halogenated organic pollutants (HOPs) in marine fish from the Beibu Gulf, South China Sea: Levels, distribution, and health risk assessment. (December 2022) - Zhu, Liang; Wang, Caiguang; Huang, Liangliang; Ding, Yang; Cheng, Yanan; Rad, Saeed; Xu, Peng; Kang, Bin
Abstract: Six marine fish species, collected from the Beibu Gulf were statistically analyzed for polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), and dichlorodiphenyltrichloroethanes (DDTs). The concentrations of ∑14 PBDEs, ∑26 PCBs, and ∑6 DDTs ranged from 11.8–1431, 8.74–495, and 9.47–1263 ng g −1 lipid weight (lw), respectively. In general, PBDEs were the predominant halogenated organic pollutants (HOPs) in the Beibu Gulf. The homologues profiles of Mugil cephalus and Trichiurus nanhaiensis differed from other four species. For example, the contributions of deca-BDEs in M. cephalus (14 %) and T. nanhaiensis (1 %) were lower than other four species (56 %). The ratio of (DDE + DDD)/ΣDDTs in all samples was >0.5, indicating that DDTs were mainly derived from historical residues. Intakes of HOPs through the consumption of the marine fish from the study areas might not subject residents of the coastal areas in the Beibu Gulf to health risks. Graphical abstract: Unlabelled Image Highlights: PBDEs were the predominant halogenated organic pollutants (HOPs) in the Beibu Gulf. The homologues profiles of migratory fish differed from the other four species in the Beibu Gulf. DDTs in the study areas was mainly derived from historical residues. The HOPs of marine fish might not pose a risk to human health.